Optimization of the Halal Fashion Industry Based on Islamic Boarding Schools in Tasikmalaya City - Danial Kusumah; Irwan Fauzy Ridwan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Tasikmalaya City is known as a center for embroidery industry which holds significant potential in the production of halal fashion industry. This potential is distributed throughout the city of Tasikmalaya with various motifs tailored to market demands. The halal fashion industry in Tasikmalaya operates at various scales, ranging from large textile factories to small-scale factories and home industries producing finished garments. Furthermore, the establishment of halal fashion industries based on pesantren (Islamic boarding schools) provides additional support, as the production process is often under the supervision of religious scholars, ensuring compliance with Islamic Sharia principles at every stage of production. This strengthens the aspect of product halal certification and maintains product quality in accordance with Islamic principles. To support the growth of this industry, there is a need for facilities that serve as production, promotion, and marketing hubs, especially for halal fashion industries, which have the potential to drive the local economy in the Tasikmalaya city area. This research becomes crucial when the management of the Tasikmalaya region is well-coordinated by the government with the support of private sectors, pesantren, and the community. Therefore, the author conducted a study aimed at analyzing the process of developing the potential of the halal fashion industry in Tasikmalaya City using the pentahelix model, employing qualitative research methods with a case study research approach. The results of this study indicate that the potential of the halal fashion industry in Tasikmalaya City can develop rapidly if all stakeholders collaborate synergistically, as reflected in the correlation among the elements in the pentahelix model.